2022
DOI: 10.1126/sciadv.abm6570
|View full text |Cite
|
Sign up to set email alerts
|

ATP-responsive biomolecular condensates tune bacterial kinase signaling

Abstract: Biomolecular condensates formed via liquid-liquid phase separation enable spatial and temporal organization of enzyme activity. Phase separation in many eukaryotic condensates has been shown to be responsive to intracellular adenosine triphosphate (ATP) levels, although the consequences of these mechanisms for enzymes sequestered within the condensates are unknown. Here, we show that ATP depletion promotes phase separation in bacterial condensates composed of intrinsically disordered proteins. Enhanced phase s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 60 publications
0
50
0
Order By: Relevance
“…The ability to avoid dissolution at high levels of ADP is in contrast to observations by Saurabh et al . that showed that ATP could dissolve SpmX biomolecular condensates at concentrations at and above 2 mM 31 . This suggests that biomolecular condensation phase diagrams display varying robustness to ATP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to avoid dissolution at high levels of ADP is in contrast to observations by Saurabh et al . that showed that ATP could dissolve SpmX biomolecular condensates at concentrations at and above 2 mM 31 . This suggests that biomolecular condensation phase diagrams display varying robustness to ATP.…”
Section: Resultsmentioning
confidence: 99%
“…These membraneless compartments organize ABC transporters 10 , single-stranded (ss) DNA-binding proteins 11 , aggresomes 12 , cell division protein FtsZ 13 , BapA amyloid biofilm matrix protein 14 , circadian rhythm associated proteins 15 and carboxysomes 16 . For example, in Caulobacter crescentus , two compositionally distinct biomolecular condensates regulate a network of signaling proteins to promote asymmetric cell division 17, 18, 19 . It has been shown that histidine kinases can be regulated spatially by sensory domain stimulation 17 .…”
Section: Introductionmentioning
confidence: 99%
“…PopZ is prone to self-associating into higher-ordered dense clusters that form microdomains at the cell poles, which allow the entry of several proteins but exclude larger macromolecules, such as ribosomes or chromosomal DNA [ 55 ]. Recently, fluorescence microscopy analyses revealed that PopZ formed condensates with a spherical morphology in vitro and that IDRs of the protein molecule were necessary and sufficient for condensate formation [ 56 ]. The same authors noticed that the phase behavior of PopZ condensates was a function of protein and salt concentration.…”
Section: Bacterial Proteins With a Potential Propensity For Liquid–li...mentioning
confidence: 99%
“…In many cases, these structures provide a basis for controlling chemical reactions or are themselves affect by reactions. Examples include chemically fueled assemblies [9][10][11][12] and membrane-less compartments that control reactions in biological cells [13][14][15][16], which are also often regulated using chemical modifications of the involved biomolecules [16][17][18][19][20][21]. In fact, chemically controlled droplets might explain how cells originated at the origin of life [22][23][24].…”
Section: Introductionmentioning
confidence: 99%